Effects of long-term anti-ischemic drug treatment on Na,K-ATPase isoforms in cardiomyopathic hamsters - Maixent, Jean Michel; Pierre, Sandrine V.; Sadrin, Stéphane; Guieu, Régis; Paganelli, Franck (Cellular and Molecular Biology, 2021)
We investigated the effects of long-term anti-ischemic therapy with trimetazidine on Na,K-ATPase (NKA) activity and protein expression in cardiomyopathy. NKA isoforms in membrane fractions from cardiomyopathic hamsters of the BIO 14.6 strain were studied and compared with those from healthy Syrian golden hamsters (F1B). Trimetazidine was orally administered to a subset of cardiomyopathic hamsters in the early stage of active disease (30 days) until the congestive stage (350 days). In the congestive stage of cardiac failure, the cardiomyopathic hamsters displayed altered NKA activity (-55 % vs. F1B; p<0.01), which was related to a specific decrease in abundance of the membrane NKA ?1 isoform (-27 % vs. F1B). Trimetazidine partially prevented the cardiomyopathy-induced changes in NKA activity (+38 %) and ?1 membrane expression (+ 66 %) without inducing changes in the expression of the ?2 isoform or 1 isoform of NKA. Cardiac hypertrophy and remodeling were reduced after trimetazidine treatment. Additionally, the abundance of NKA ?1 in membranes was negatively correlated with the ventricular weight/body weight ratio (an index of cardiac hypertrophy) (r2 = 0.99; p<0.0015). These findings suggest that some of the cardioprotective effect of trimetazidine during long-term cardiomyopathy may be achieved via regulation of cardiac remodeling and selective modulation cardiac NKA isoforms.